What Matters In Language And Literacy In The Early Years: Exploring Teacher’s Viable Strategies For Promoting Children’s Language Development And Literacy Skills - Rahimah Saimin; Saiful Izwan Zainal (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
International Language and Education Conference 2021 (iLEC’21) e-PROCEEDINGS “Language and Education : New Norms” 2nd & 3rd November 2021 Organized by : Faculty of Major Language Studies (FPBU), USIM Editor: Azalia Zaharuddin, Suhaili A. Jalil, Kirembwe Rashid Abdul Hameed, Wan Azura Wan Ahmad.